Meningkatkan Keterampilan Vokasional Membuat Vas Bunga dari Gelas Minuman Bekas Melalui Metode Demonstrasi Bagi Anak Tunagrahita Ringan - Hakim, Mayang Permata; Z, Martiaz (Inovan Publisher, 2024)
This study discusses how to improve vocational skills in making flower vases from used drink glasses for children with mental retardation through demonstration methods. This research uses classroom action research. This classroom action research was conducted in class X SLB Negeri 1 Lubuk Sikaping. The problem behind the implementation of this research was that in class X SLB Negeri 1 Lubuk Sikaping had learned how to make flower vases from used drink glasses, but there were students who were not skilled in making flower vases from used drink glasses. This research will be conducted in two cycles, each of which consists of: planning, implementing the action, observing and reflecting. The data collection techniques used were observation, documentation, and action tests. The results obtained by students using two cycles, student AG value in the first cycle of action is 71%, and in the second cycle obtained a value of 96%, while student LH value in cycle I is 68%, and in cycle II obtained a value of 93 %, then student MA in cycle I obtained a value of 71%, and in cycle II obtained a value of 93%. Based on the data above, the conclusion of the skill of making flower vases from used beverage glasses has increased significantly through the demonstration method.